Mental development is associated with cortical connectivity of the ventral and nonspecific thalamus of preterm newborns. Issue 10 (13th August 2020) - Jakab, Andras; Natalucci, Giancarlo; Koller, Brigitte; Tuura, Ruth; Rüegger, Christoph; Hagmann, Cornelia
Abstract: Introduction: The thalamus is a key hub for regulating cortical connectivity. Dysmaturation of thalamocortical networks that accompany white matter injury has been hypothesized as neuroanatomical correlate of late life neurocognitive impairment following preterm birth. Our objective was to find a link between thalamocortical connectivity measures at term equivalent age and two‐year neurodevelopmental outcome in preterm infants. Methods: Diffusion tensor MRI data of 58 preterm infants (postmenstrual age at birth, mean ( SD ), 29.71 (1.47) weeks) were used in the study. We utilized probabilistic diffusion tractography to trace connections between the cortex and thalami. Possible associations between connectivity strength, the length of the probabilistic fiber pathways, and developmental scores (Bayley Scales of Infant Development, Second Edition) were analyzed using multivariate linear regression models. Results: We found strong correlation between mental developmental index and two complementary measures of thalamocortical networks: Connectivity strength projected to a cortical skeleton and pathway length emerging from thalamic voxels (partial correlation, R  = .552 and R  = .535, respectively, threshold‐free cluster enhancement, corrected p ‐value < .05), while psychomotor development was not associated with thalamocortical connectivity. Post hoc stepwise linear regression analysis revealed that parental socioeconomic scale, postmenstrual age, and the duration of mechanical ventilation at the intensive care unit contribute to the variability of outcome. Conclusions: Our findings independently validated previous observations in preterm infants, providing additional evidence injury or dysmaturation of tracts emerging from ventral‐specific and various nonspecific thalamus projecting to late‐maturing cortical regions are predictive of mental, but not psychomotor developmental outcomes. Abstract : Our purpose was to find a link between thalamocortical connectivity measures at term equivalent age and two‐year neurodevelopmental outcome in 58 infants following preterm birth. Using probabilistic diffusion tractography, we found that injury or dysmaturation of tracts emerging from ventral‐specific and various nonspecific thalamus projecting to late‐maturing cortical regions is predictive of mental, but not psychomotor developmental outcomes